2011
DOI: 10.1161/circep.110.957126
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low Interatrial Septum and Right Atrial Appendage Pacing for Prevention of Permanent Atrial Fibrillation in Patients With Sinus Node Disease

Abstract: Background-The role of pacing sites and atrial electrophysiology on the progression of atrial fibrillation (AF) to the permanent form in patients with sinus node dysfunction (SND) has never been investigated. The aim of the study was to investigate the relationship between atrial electrophysiology and the efficacy of atrial pacing at the low interatrial septum (IAS) or at the right atrial appendage (RAA) to prevent persistent/permanent AF in patients with SND. Methods and Results-The Electrophysiology-Guided P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 27 publications
(32 reference statements)
2
35
0
Order By: Relevance
“…This, compared with RAA pacing, may decrease the rate of unnecessary ventricular pacing . The EPASS study showed that LRAS is more effective that RAA pacing in the prevention of persistent AF in patients with SND and intraatrial conduction delays . Wang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, compared with RAA pacing, may decrease the rate of unnecessary ventricular pacing . The EPASS study showed that LRAS is more effective that RAA pacing in the prevention of persistent AF in patients with SND and intraatrial conduction delays . Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…The low right atrial (RA) septum has been suggested as an alternate pacing site, instead of the RA appendage (RAA), for a more effective prevention of atrial fibrillation (AF) in selected pacemaker recipients presenting with sinus node disease (SND), though this remains controversial. [1][2][3][4][5][6] Episodes of AF can be triggered in presence of predisposing factors, such as sinus bradycardia, atrial ectopy, short-long-short sequences, increased dispersion of atrial refractoriness and locally inhomogeneous intraatrial conduction. In the MOST 7 and the SavePace trials, 8 a high cumulative percentage of ventricular pacing (cum%VP) in patients with SND was associated with a high incidence of AF, particularly when paced at the right ventricular (RV) apex.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have observed that in patients with sinus node disease and intra-atrial conduction delay at the posterior angle of Koch, low interatrial pacing is superior compared to right atrial appendage pacing in preventing progression to persistent or permanent AF and is associated with the shortest atrial activation time compared with other atrial septal pacing sites in patients with IAB [32, 69, 70]. …”
Section: Common Myths and Under-known Facts About Iabmentioning
confidence: 99%
“…Allostatic capacity can be monitored by the activity of the autonomic nervous system (ANS) through its regulation of the cardiovascular, respiratory and neuroendocrine systems (Verlato et al, 2011). The analysis of cardiovascular control, termed heart rate variability (HRV), has been as reported as an effective tool to identify changes in ANS activity (Task Force, 1996) in response to different stressors (Teisala et al, 2014).…”
Section: Introductionmentioning
confidence: 99%